2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6091379
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of scarred and non-scarred myocardium in LG enhanced CMR images using intensity-based textural analysis

Abstract: The Late Gadolinium (LG) enhancement in Cardiac Magnetic Resonance (CMR) imaging is used to increase the intensity of scarred area in myocardium for thorough examination. Automatic segmentation of scar is important because scar size is largely responsible in changing the size, shape and functioning of left ventricle and it is a preliminary step required in exploring the information present in scar. We have proposed a new technique to segment scar (infarct region) from non-scarred myocardium using intensity-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The use of native T1 mapping for post-acute MI without use of contrast would be of major clinical use, in that it would not only be safer in patients with kidney impairment and would shorten the scan time (by avoiding contrastbased techniques) but would also potentially allow for an early accurate stratification of those acute patients in need of more aggressive treatment (30). Furthermore, TA based on T1 mapping, as it includes more information, may be used to assess the high risk of arrhythmia patients to implant ICD (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…The use of native T1 mapping for post-acute MI without use of contrast would be of major clinical use, in that it would not only be safer in patients with kidney impairment and would shorten the scan time (by avoiding contrastbased techniques) but would also potentially allow for an early accurate stratification of those acute patients in need of more aggressive treatment (30). Furthermore, TA based on T1 mapping, as it includes more information, may be used to assess the high risk of arrhythmia patients to implant ICD (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…PIZ was defined as area with an SI between 2 and 3 SD above SI of remote myocardium, normalized as a percentage of total infarct zone (area with an SI of > 2 SD above remote myocardium). Roes et al [79] found that PIZ was the strongest predictor for spontaneous VT. Based on the potential limitation of using the peak SI of remote myocardium to define PIZ, core infarct and PIZ were based exclusively on the maximum SI in the hyperenhanced area (core SI ≥ 50% of maximal SI, grey zone 35% ≤ SI < 50% of maximum SI) [80,81]. However, at the moment there are no data about the definite role of PIZ in the SCD prediction.…”
Section: Coronary Artery Diseasementioning
confidence: 99%
“…Previous studies reported an improvement in detection of scarred myocardium on LGE images when combining texture and intensity features . Texture analysis was also used to create probability maps using LGE images that aid the visual inspection of the myocardial tissue .…”
Section: Introductionmentioning
confidence: 99%